تفاسير المفسرين القدماء للآيتين 75 و76 من سورة النحل Tafasir al-mufassirin al-qudama' li-l-ayatayn 75 wa 76 min surat al-Nahl (Ancient Interpretations of Surat an-Nahl 75 & 76) - Hoover, Jon (Near East School of Theology, 2007)
This article in Arabic surveys interpretations of the parabolic imagery in Qur'an 16:75-76 found in the classical commentators al-Tabari (d. 923), al-Razi (d. 1209), al-Qurtubi (d. 1272), al-Baydawi (d. 1282 or 1291), Ibn Kathir (d. 1373) and al-Jalalayn--Jalal al-Din al-Mahalli (d. 1459) and Jalal al-Din al-Suyuti (d. 1505).